Exploring the potential of a hybrid device combining solar water heating and molecular solar thermal energy storage. Issue 3 (28th November 2016) - Dreos, Ambra; Börjesson, Karl; Wang, Zhihang; Roffey, Anna; Norwood, Zack; Kushnir, Duncan; Moth-Poulsen, Kasper
Abstract : A hybrid solar energy system consisting of a molecular solar thermal energy storage system (MOST) combined with a solar water heating system (SWH) is presented. Abstract : A hybrid solar energy system consisting of a molecular solar thermal energy storage system (MOST) combined with a solar water heating system (SWH) is presented. The MOST chemical energy storage system is based on norbornadiene–quadricyclane derivatives allowing for conversion of solar energy into stored chemical energy at up to 103 kJ mol −1 (396 kJ kg −1 ). It is demonstrated that 1.1% of incoming solar energy can be stored in the chemical system without significantly compromising the efficiency of the solar water heating system, leading to efficiencies of combined solar water heating and solar energy storage of up to 80%. Moreover, prospects for future improvement and possible applications are discussed.